Utilizing marine algal metabolites to fight neurodegenerative diseases - Naik, Bindu; Richa, Shruti; Bharadwaj, Shivangi; Mishra, Sadhna; Kumar, Vijay; Kumar, Vivek; Saris, Per Erik Joakim; Gupta, Arun Kumar; Mishra, Ritesh; Gupta, Uttam; Rustagi, Sarvesh; Preet, Manpreet Singh (Frontiers in Marine Science, 2024)
Marine algae are thought to be a source of various metabolites that have a wide range of positive effects on human health. The pharmacological properties of algal metabolites, including their antioxidant, anti-inflammatory, cholesterol homeostasis, protein clearance, and anti-amyloidergic effects, lend credence to their protective efficacy against oxidative stress, neuroinflammation, mitochondrial dysfunction, and impaired proteostasis, all of which are involved in the pathophysiology of neurodegenerative disorders. There are currently no clinical trials on the effects of marine algae on neuroinflammation; however, considering the significant biological activities that have been established by in vitro and animal research, we expect that there will be clinical trials on this topic in the not-too-distant future. The most recent and important findings on the potentially neuroprotective effects of the anti-inflammatory properties of marine algae were chosen for this study. Next, we conducted a literature review on the neuroprotective potential of algal compounds, along with the underlying pharmacological mechanism, and finally, we evaluated recent advances in therapeutics.